2013
DOI: 10.3389/fphys.2013.00200
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila melanogaster larvae control amylase secretion according to the hardness of food

Abstract: Drosophila melanogaster larvae excrete amylase and perform external digestion of their food. In this study, to investigate whether their external digestion ability varies in response to changes in the external environment, we measured the relative amount of amylase excreted by larvae using a new method: the iodine starch agar method (ISAM). Analysis using this method revealed that the amount of amylase excreted by larvae increased in accordance with the increase in the agar concentration. In addition, we inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Additionally, before they can reach the lower nutritious resources, the pioneers must expend energy digging a hole that may collapse (and suffocate them), with the likelihood of failure increasing if others in the group abandon the cluster prematurely. Finally, before they can be consumed, the unexploited resources may first need to be ‘socially digested’ via the production and excretion of digestive enzymes of the pioneering larvae (Gregg et al., , Sakaguchi and Suzuki, ). Thus, there are few immediate benefits and considerable uncertainties, investments and risks involved in initiating a feeding cluster.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, before they can reach the lower nutritious resources, the pioneers must expend energy digging a hole that may collapse (and suffocate them), with the likelihood of failure increasing if others in the group abandon the cluster prematurely. Finally, before they can be consumed, the unexploited resources may first need to be ‘socially digested’ via the production and excretion of digestive enzymes of the pioneering larvae (Gregg et al., , Sakaguchi and Suzuki, ). Thus, there are few immediate benefits and considerable uncertainties, investments and risks involved in initiating a feeding cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, before they can be consumed, the unexploited resources may first need to be 'socially digested' via the production and excretion of digestive enzymes of the pioneering larvae (Gregg et al, 1990, Sakaguchi andSuzuki, 2013). Thus, there are few immediate benefits and considerable uncertainties, investments and risks involved in initiating a feeding cluster.…”
Section: Discussionmentioning
confidence: 99%
“…Olfaction is key to the survival of Drosophila larvae: attractive odors guide larvae towards food sources ( Asahina et al, 2008 ; Gomez-Marin and Louis, 2012 ). Feeding in larvae is also facilitated by the aggregation of groups of larvae that expel digestive enzymes in their saliva — a process called social digestion ( Gregg et al, 1990 ; Sakaguchi and Suzuki, 2013 ). Spatial aggregation of larvae relies on the detection of pheromones ( Mast et al, 2014 ; Del Pino et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of Sakaguchi and Suzuki (2013) with Drosophila melanogaster suggested that increasing the amylase content of the food medium had the same effect on the larval growth rate as that observed in the large population group. It is conceivable that the addition of amylase to the food increases its glucose content, which in turn may have caused the pupation delay.…”
mentioning
confidence: 85%